P371 Outcome of immediate infliximab optimisation based on rapid assessment of serum drug and faecal calprotectin concentrations in Crohn's disease. (25th January 2019) - Farkas, K; Szántó, K; Kata, D; Bálint, A; Milassin, Á; Fábián, A; Bor, R; Rutka, M; Szepes, Z; Soós, I; Nagy, F; Földesi, I; et al.
Abstract: Background: Dose intensification strategy based on the parallel assessment of clinical symptoms, serum and faecal biomarkers and serum infliximab (IFX) concentration may increase therapeutic response in inflammatory bowel diseases. The aim of this study was to evaluate the outcome of IFX optimisation based on proactive drug monitoring in combination with the assessment of clinical activity and biomarkers using rapid assays. Methods: This is a prospective study of Crohn's disease (CD) patients on IFX maintenance therapy, started in May 2018. Blood and faecal samples were obtained at the day when subsequent IFX infusion was scheduled. C-reactive protein (CRP) and haematocrit levels were measured immediately. Serum IFX and faecal calprotectin (FC) concentrations were benchmarked with rapid, lateral flow-based assays (RIDA®QUICK, Quantum Blue®). Clinical activity indices (CDAI) were calculated at the same visit. On the basis of all data, patients were assigned to 4 groups: no intervention (NI) if CRP < 10 mg/l AND FC < 300 µg/g, AND CDAI < 200, AND IFX level was 3–10 µg/ml. Dose increase (DI) if either CRP, FC or the activity indices were elevated, OR IFX level was lower than 3 µg/ml. Stopping IFX (ST) if all the activity markers were in normal range but IFX were undetectable or is in very low concentration. Switch if any of the activity markers were abnormal AND serum IFX were in sub or supra therapeutic level. After optimisation, patients are followed for 6 months with determining all the above-mentioned parameters retrospectively at every 2 month. Results: Data of 26 CD patients were available to be analysed with a 4 months follow-up. On the basis of the rapid tests, DI was performed in 14 patients, NI in 8 patients, and ST in 4 patients. In DI group, serum level of IFX increased, CDAI decreased significantly at month 2 and 4 compared with the baseline. Level of CRP and FC did not change significantly at month 2, but CRP decreased significantly at month 4. After the dose increase, 2 patients had subtherapeutic drug level with antibody positivity at every examined time point. One patient had to be hospitalised because of a relapse and was switched to ustekinumab. All patients in NI group remained in remission at month 2 and 4. None of the examined parameters, except for serum IFX level at month 4 changed significantly at month 2 and 4. One patient in the ST group required reintroduction of therapy with adalimumab at month 2; the other 3 patients were still in remission at month 2 and 4. Conclusions: Change in therapy was performed in 18 cases on the bases of benchmarked concentrations of serum IFX and FC levels. Our results suggest benefit of using rapid tests in daily practice. The study is ongoing to evaluate medium- and long-term benefits.